ISOLASI, PEMURNIAN PARSIAL DAN KARAKTERISASI CRUDE ENZIM DARI BAKTERI PENDEGRADASI FENOL - Marliana, Diah
Abstract: Phenol is commonly found in the effluent of oil refinery, petrochemical plant and textile industry. This compound is toxic and carcinogenic. This research was conducted to isolate microorganism capable of degradation phenol in aerobic batch reactor, to characterize the partially purified enzyme. The bacterium used in this study is Pseudornonas pseudoalcaligenes isolated from oil-contaminated soil around the installation of Unit Pengolahan VI Balongan, Indramayu. Enzyme was isolated by ultrasonication and centrifugation followed by purification using ammonium sulphate fractionation and DEAE-cellulose anion exchanger column chromatography. The result showed that the optimum growth of bacterium was at 1000 mg/L phenol concentration and temperature at 40°C. At phenol concentration of 250 - 1250 mg/L, the specific growth rate were 0.2215 - 0.2461 hour' and the phenol degradation rate were 0.268 - 0.3855 hour-' with the phenol degradation efficiency were 99.6 - 100 %. Phenol biodegradation kinetics showed maximum specific growth rate (µm) was 0.24495 hour -' and substrate affinity constant (Ks) was 30.05 mg/L. The result of isolation and purification showed specific activity crude enzyme, ammonium sulphate fraction and DEAE-cellulose anion exchanger column chromatography fraction were 0.767, 0.944 and 74.3 unit/mg protein respectively. The purified enzyme has an optimum activity at pH 7.0 and optimum temperature at 40°C, maximum specific activity (V,,,)) value was 129.87 Unit/mg protein whereas Km was 52.3376 }AM. One unit of enzyme activity is defined as 1 µmol of phenol conversion per minute.